Unequal refugeeness : Race, gender, and co-belligerence from Poles in colonial Africa to Ukrainians in Poland - Lingelbach, Jochen (Journal of Refugee Studies, 2025)
Refugee-receiving states do not live up to the universalist ideals of international refugee legislation but are selective and discriminatory. The case of Poland’s acceptance of Ukrainians while simultaneously building a border wall to keep out non-Ukrainians is an obvious case. Based on historical research on the British Empire’s policies towards European refugees, this article looks into a comparable moment when governments made an exception to their established anti-refugee policy and accepted certain groups of refugees. The British colonial administration in East Africa rejected Jewish refugees but accepted a specific group of Poles during the Second World War. This exception under war conditions was legitimized with an emphasis on the group’s gender, race, and connection to the co-belligerent Polish army. They were the white women and children of the Polish male soldiers fighting with the British against the Axis. The recent welcome for Ukrainian refugees in Poland followed similar lines of argumentation.
Keywords: Race; Poland; Colonialism; Ukraine; War; History; Refugees